Cell vacuolation induced by Haemophilus influenzae supernatants in HEp-2 cells - Maria del Rosario Espinoza-Mellado; Edgar Oliver Lopez-Villegas; Ramon I Arteaga-Garibay; Silvia Giono-Cerezo (Memorias do Instituto Oswaldo Cruz, 2013)
Haemophilus influenzae belongs to respiratory tract microbiota. We observed vacuoles formation in previous studies with H. influenzae culture supernatants, so in this work we characterised that cytotoxic effect. We observed an abundant production of acidic cytoplasmic vacuoles due to the presence of a “vacuolating factor” in H. influenzae supernatants which was characterised as thermolabile. Greatest vacuolating activity was observed when utilizing the fraction > 50 kDa. The presence of a large number of vacuoles in HEp-2 cells was verified by transmission electron microscopy and some vacuoles were identified with a double membrane and/or being surrounded by ribosomes. These results suggest similar behaviour to that of vacuolating effects described by autotransporter proteins an undescribed cytotoxic effect induced by H. influenzae .